CRIGLER- NAJJAR SYNDROME - CASE REPORT - Anja Šelih; Manca Velkavrh (The Society for Children with Metabolic Disorders, 2022)
Crigler-Najjar syndrome is a rare genetic disorder that causes severe unconjugated hyperbilirubinaemia. The syndrome is caused by a mutation in the UGT1A1 gene, which results in a deficiency or complete lack of the UGT1A1 enzyme, which is responsible for the conjugation of bilirubin. If the disease remains unrecognised or untreated it can cause severe neu-rological consequences. on a patient and his family. The key to a good prognosis is aggressive treatment of unconjugated hyperbilirubinaemia with phototherapy as soon as possible. The life expectancy and the quality of life of people with Crigler-Najjar syndrome have improved greatly with the use of phototherapy and other therapeutic methods. At the moment, the only cure is liver transplantation with some potential treatments still in the phase of clinical trials.